Policy words and policy deeds: the ECB and the euro - Pierre Siklos; Martin Bohl (Bank of Finland, 2006)
This paper examines the role of the ECB communication activities on daily Eurodollar exchange rate and interest rates.We estimate the relationship between monetary policy and the exchange rate using a technique that explicitly recognises the joint determination of both the levels and volatilities of these variables.We also consider more traditional estimation strategies as a test of the robustness of our main results.We introduce a new indicator of ECB communications policies that focuses on what the ECB says about the future economic outlook for the euro area along five different economic dimensions.The impact of ECB communications policies is more apparent in the time series framework than in the heteroskedasticity estimator approach.Previous studies that conclude that news effects are significant at the daily frequency may have reached such a conclusion because the measurement of news was too highly aggregated.The endogeneity of the exchange rate - interest rate relationship is more apparent when the proxy for monetary policy is the euro area - US differential than when any other proxy for monetary policy is employed.Finally, interest rate changes generally have a much larger impact on exchange rate movements, and their volatility, than do ECB verbal pronouncements.
URN:NBN:fi:bof-20140807533
Keywords: F3; E5; E6; 330; communication policy; exchange rates; interest rates; volatility